Diaphragm, preparation method thereof and secondary battery
By applying hydrophobically modified metal oxides to form a solid electrolyte layer on the separator body, the problem of excessive moisture content of the oxide solid electrolyte coating separator is solved, and the performance of the secondary battery is significantly improved.
Patent Information
- Application Number
- CN202311230280.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
The existing oxide solid electrolyte-coated separators have excessive moisture content due to hydrophilic properties, which affects the cycling and safety performance of the battery.
By applying hydrophobically modified metal oxides to the separator body and forming a solid electrolyte layer, the moisture content value of the solid electrolyte coated separator is reduced. The modified metal oxide includes a metal oxide and a silane compound attached to the surface of the metal oxide.
It significantly reduces the moisture content of the diaphragm, alleviates the negative impact of moisture on battery performance, improves the Coulomb efficiency and circulation performance of the secondary battery, and improves the safety performance of the battery.
Smart Images

Figure CN119674423A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a diaphragm and a preparation method thereof, and a secondary battery. Background Art
[0002] In recent years, new energy electric vehicles have developed rapidly. Among them, the core components of electric vehicles come from power batteries. The performance of power batteries determines the performance of electric vehicles to a certain extent. The main performance of power batteries includes energy density, cycle, fast charging and safety performance. In order to improve energy density and safety performance, lithium-ion battery technology is also constantly improving and developing, such as from the current liquid battery to semi-solid battery and all-solid battery. There is no liquid electrolyte in the all-solid battery, and lithium metal negative electrode can be used, which can greatly improve the energy density and safety performance of the battery. However, because there is no electrolyte to conduct lithium ions in the all-solid battery, the internal resistance of the battery is too large, and its application in power batteries is not yet mature. Semi-solid batteries are a transitional form in the process of transformation between liquid batteries and solid-state batteries. They improve the overall safety performance of the battery by reducing the amount of electrolyte used. With the development of semi-solid battery technology, solid electrolyte coated diaphragms have also come into being.
[0003] However, the current separators, preparation methods thereof, and secondary batteries still need to be improved. Summary of the invention
[0004] In semi-solid batteries, oxide solid electrolytes are usually mixed in positive and negative electrode materials or coated on the surface of the diaphragm to form oxide solid electrolyte diaphragms. The inventors found that the current oxide solid electrolyte coated diaphragms, due to the hydrophilic properties of the oxide solid electrolyte itself, can reach a moisture value of more than 3000ppm in the process of using water-based coating technology, which is much higher than the current ceramic (such as alumina and boehmite) coated diaphragms. Even if the solid electrolyte coated diaphragm is baked, its moisture is difficult to reduce to less than 1000ppm. Due to excessive moisture, the cycle performance of the battery is negatively affected. For example, moisture will react with lithium hexafluorophosphate (LiPF6) in the electrolyte to generate HF, thereby deteriorating the cycle performance. During high-temperature cycles, it is more likely to produce gas. In order to solve or alleviate at least one of the above problems, the present application provides a diaphragm and a preparation method thereof, and a secondary battery. By coating a hydrophobically modified metal oxide on the diaphragm body and forming a solid electrolyte layer, the moisture value of the solid electrolyte coated diaphragm is significantly reduced, thereby alleviating the negative impact of diaphragm moisture on battery performance, and improving the coulombic efficiency and cycle performance of the secondary battery using the diaphragm.
[0005] One aspect of the present application provides a diaphragm, which includes: a diaphragm body; a solid electrolyte layer, wherein the solid electrolyte layer is arranged on the diaphragm body, and the solid electrolyte layer includes a modified metal oxide, and the modified metal oxide includes a metal oxide and a silane compound connected to the surface of the metal oxide, wherein the metal oxide includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium lanthanum aluminum titanate.
[0006] Another aspect of the present application provides a method for preparing a diaphragm, which includes: providing a mixed solution containing a silane compound and a first solvent; mixing a metal oxide with the mixed solution, and forming a modified metal oxide through reaction treatment; wherein the metal oxide includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium lanthanum aluminum titanate; forming the first slurry on the diaphragm body, and forming the diaphragm through drying treatment.
[0007] Another aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate and the above-described diaphragm or a diaphragm formed by the above-described preparation method; wherein the solid electrolyte layer in the diaphragm is arranged toward the negative electrode plate.
[0008] The beneficial effects of this application are:
[0009] The diaphragm of the present application is formed by coating a hydrophobically modified metal oxide on the diaphragm body and forming a solid electrolyte layer. On the one hand, the diaphragm has excellent ionic conductivity, which reduces the internal resistance of the secondary battery using the diaphragm; and, in current secondary batteries, transition metal ions (such as manganese) dissolved from the positive electrode plate are easily migrated to the surface of the negative electrode plate, thereby destroying the solid electrolyte interface film (SEI film) on the surface of the negative electrode plate and deteriorating the negative electrode plate. The present application arranges a solid electrolyte layer on the diaphragm body, and the modified metal oxide therein will be reduced by the negative electrode plate during the battery discharge process, forming a dense film structure on the diaphragm surface, thereby preventing the transition metal ions from depositing on the surface of the negative electrode plate, that is, the solid electrolyte layer in the diaphragm can reduce the migration of transition metal ions (such as manganese) dissolved from the positive electrode plate side to the surface of the negative electrode plate, thereby improving the negative electrode plate. The stability of the SEI film on the surface of the pole piece reduces side reactions, thereby improving the safety and cycle performance of the battery; on the other hand, the solid electrolyte with high moisture content in the current diaphragm will cause serious high-temperature gas production in the battery cell. After the metal oxide is surface-modified by a silane compound, the hydrophobic group (such as at least one of an amine group, an olefin group, and an epoxy group) in the silane compound is connected to the surface of the metal oxide, and a hydrophobic layer is formed on the surface of the metal oxide. When the hydrophobic modified metal oxide is aqueously coated on the diaphragm body, the contact and penetration of water with the modified metal oxide powder is reduced, and the dispersion performance of the modified metal oxide in an oily organic solvent is improved. The diaphragm finally obtained significantly reduces its moisture value, alleviates the problem of high-temperature gas production of the battery cell caused by high moisture content in the diaphragm, and improves the coulomb efficiency and cycle performance of the secondary battery using the diaphragm. Therefore, based on the above improvements, the secondary battery using the diaphragm in this application has at least one of the following advantages: excellent coulomb efficiency, cycle performance, and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to make the above-mentioned purpose, features and advantages of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein, so the present invention is not limited to the specific embodiments disclosed below.
[0011] Figure 1 A schematic diagram showing a contact angle test of a solid electrolyte layer formed by an unmodified metal compound;
[0012] Figure 2 The schematic diagram of contact angle test of the solid electrolyte layer formed by the modified metal compound according to the present application is schematically shown. DETAILED DESCRIPTION
[0013] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0014] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0015] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0016] The selection range of the terms "and / or", "or / and", and "and / or" includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, and the said any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and undoubtedly includes technical solutions that are all connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four of A, B, C, and D (that is, the technical solution that is all connected by "logical AND").
[0017] The term "C1-C6 alkoxy" may be methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentyloxy or n-hexyloxy.
[0018] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0019] 1. Diaphragm
[0020] One aspect of the present application provides a diaphragm, which includes: a diaphragm body; a solid electrolyte layer, the solid electrolyte layer is arranged on the diaphragm body, the solid electrolyte layer includes a modified metal oxide, the modified metal oxide includes a metal oxide and a silane compound connected to the surface of the metal oxide, wherein the metal oxide includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium lanthanum aluminum titanate.
[0021] The diaphragm of the present application is formed by coating a hydrophobically modified metal oxide on the diaphragm body and forming a solid electrolyte layer. On the one hand, the diaphragm has excellent ionic conductivity, which reduces the internal resistance of the secondary battery using the diaphragm; and, in current secondary batteries, transition metal ions (such as manganese) dissolved from the positive electrode plate are easily migrated to the surface of the negative electrode plate, thereby destroying the solid electrolyte interface film (SEI film) on the surface of the negative electrode plate and deteriorating the negative electrode plate. The present application sets a solid electrolyte layer on the diaphragm body, and the modified metal oxide therein will be reduced by the negative electrode plate during the battery discharge process, forming a dense film structure on the diaphragm surface, thereby preventing the transition metal ions from depositing on the surface of the negative electrode plate, that is, the solid electrolyte layer in the diaphragm can reduce the migration of transition metal ions (such as manganese) dissolved from the positive electrode plate side to the surface of the negative electrode plate, thereby improving the SEI film on the surface of the negative electrode plate. stability, reducing side reactions, thereby improving the safety and cycle performance of the battery; on the other hand, the solid electrolyte with high moisture content in the current diaphragm will cause serious high-temperature gas production in the battery cell. After the metal oxide is surface-modified by a silane compound, the hydrophobic group (such as at least one of an amine group, an olefin group, and an epoxy group) in the silane compound is connected to the surface of the metal oxide, and a hydrophobic layer is formed on the surface of the metal oxide. When the hydrophobic modified metal oxide is aqueously coated on the diaphragm body, the contact and penetration of water and the modified metal oxide powder are reduced, and the dispersion performance of the modified metal oxide in an oily organic solvent is improved. The diaphragm finally obtained significantly reduces its moisture value, alleviates the negative impact of the diaphragm moisture on the battery performance, alleviates the problem of high-temperature gas production of the battery cell caused by high moisture content in the diaphragm, and improves the coulomb efficiency and cycle performance of the secondary battery using the diaphragm. Therefore, based on the above improvements, the secondary battery using the diaphragm in this application has at least one of the following advantages: excellent coulomb efficiency, cycle performance, and safety performance.
[0022] In some embodiments, when the diaphragm is used in a secondary battery, the diaphragm is disposed between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte layer is disposed toward the negative electrode sheet. Thus, the solid electrolyte layer faces the negative electrode sheet, and the modified metal oxide therein will be reduced during the battery discharge process, forming a dense film structure on the surface of the diaphragm, thereby preventing transition metal ions from depositing on the surface of the negative electrode sheet, that is, the solid electrolyte layer in the diaphragm can reduce the migration of transition metal ions (such as manganese) dissolved from the positive electrode sheet side to the surface of the negative electrode sheet, thereby improving the stability of the SEI film on the surface of the negative electrode sheet, reducing side reactions, and thereby improving the safety performance and cycle performance of the battery.
[0023] In some embodiments, the surface of the metal oxide includes a hydroxyl group (-OH), and the silane compound contains at least one C1-C6 alkoxy group connected to the silicon atom (-Si-OR, R includes a C1-C6 alkyl group). It should be noted that the C1-C6 alkoxy group connected to the silicon atom as a whole is at least one in the silane compound; in the C1-C6 alkoxy group connected to the silicon atom, the number of C1-C6 alkoxy groups connected to the silicon atom is at least one, for example, it can be one, two or three C1-C6 alkoxy groups. The silane compound is connected to the surface of the metal oxide by reacting the C1-C6 alkoxy group connected to the silicon atom with the hydroxyl group on the surface of the metal oxide. In some embodiments, the silane compound contains a hydrophobic group, and the hydrophobic group contains at least one of an amine group (-NH2), an alkenyl group (-C=C) and an epoxy group (-C(O)C-) functional group. Thus, after the silane compound is connected to the surface of the metal oxide, the hydrophobic group in the silane compound is also synchronously connected to the metal oxide surface, and the hydrophobic group can hydrophobically modify the metal oxide, and then form a hydrophobic layer on the metal oxide surface, reducing the contact and penetration of water and modified metal oxide powder. It should be noted that the surface of the metal oxide includes hydroxyl groups, which can be introduced when preparing the metal oxide, that is, a large amount of hydroxyl groups can be introduced on the surface when preparing the metal oxide. The silane compound is a silane coupling agent, and when the C1-C6 alkoxy groups connected to silicon atoms contained therein react with the hydroxyl groups on the metal oxide surface, the C1-C6 alkoxy groups connected to silicon atoms contained by the silane compound are first hydrolyzed to form silanol groups (-Si-OH), such as silane compounds are hydrolyzed in water or ethanol, and formic acid or acetic acid can be added to catalyze hydrolysis, and the silanol groups formed by the hydrolysis can react with the hydroxyl groups on the metal oxide surface, and then dehydration condensation occurs, and finally the silane compound forms a chemical bond by the reaction of the C1-C6 alkoxy groups connected to silicon atoms and hydroxyl groups, so that the silane compound is connected to the surface of the metal oxide. Therefore, after the metal oxide is surface-modified by a silane compound, the hydrophobic groups in the silane compound are also simultaneously connected to the metal oxide surface to form a hydrophobic layer on the metal oxide surface. When the hydrophobic modified metal oxide is aqueous-coated on the diaphragm body, the contact and penetration of water and the modified metal oxide powder is reduced, and the dispersion properties of the modified metal oxide in oily organic solvents are improved. The resulting diaphragm significantly reduces its moisture value, alleviates the problem of high-temperature gas production in the battery cell caused by high moisture in the diaphragm, and improves the coulombic efficiency and cycle performance of the secondary battery using the diaphragm.
[0024] In some embodiments, the contact angle of the modified metal oxide is 80° to 120°. In some embodiments, the contact angle of the modified metal oxide is 80°, 85°, 90°, 95°, 100°, 102°, 104°, 106°, 108°, 110°, 112°, 114°, 116°, 118°, 120° or any value therebetween. In some embodiments, the contact angle of the modified metal oxide is 100° to 120°. In some embodiments, the contact angle of the modified metal oxide is 105° to 115°. It should be noted that the contact angle of the modified metal oxide can be obtained by testing after pressing it into a sheet.
[0025] In some embodiments, the ion conductivity of the separator is 0.5 ms / cm to 0.9 ms / cm. In some embodiments, the ion conductivity of the separator is 0.5 ms / cm, 0.55 ms / cm, 0.6 ms / cm, 0.65 ms / cm, 0.7 ms / cm, 0.75 ms / cm, 0.8 ms / cm, 0.85 ms / cm, 0.9 ms / cm, or any value therebetween. Thus, the internal resistance of the secondary battery using the separator can be further reduced.
[0026] In some embodiments, the metal oxide includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lanthanum aluminum lithium titanate. In some embodiments, the ratio of each element in the metal oxide and the ratio of other doped elements are not particularly limited. The ratio of each element in the metal oxide and the ratio of doped elements are regulated according to demand. For example, the common molecular structure of LATP is Li 1.3 Al 0.3 Ti 1.7 (PO4)3. Thus, the ion conductivity of the separator can be improved by using the above-mentioned metal oxides having high ion conductivity.
[0027] In some embodiments, the silane compound includes at least one of γ-aminopropyl triethoxysilane (KH550), vinyl triethoxysilane, vinyl trimethoxysilane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane (KH560) and γ-methacryloxypropyl trimethoxysilane (KH570). Thus, the silane compound contains a C1-C6 alkoxy group connected to the silicon atom, and the silane compound is connected to the surface of the metal oxide through the reaction of the C1-C6 alkoxy group connected to the silicon atom and the hydroxyl group on the surface of the metal oxide; the silane compound contains a hydrophobic group, and the hydrophobic group includes at least one of an amino group, an alkenyl group and an epoxy group. After the silane compound is connected to the surface of the metal oxide, the hydrophobic group in the silane compound is also connected to the surface of the metal oxide at the same time, and the hydrophobic group can hydrophobically modify the metal oxide, thereby forming a hydrophobic layer on the surface of the metal oxide.
[0028] In some embodiments, the average particle size of the metal oxide is 0.3 μm to 3 μm. In some embodiments, the average particle size of the metal oxide is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3 or any value therebetween. In some embodiments, the average particle size of the metal oxide is 1 μm to 2 μm.
[0029] In some embodiments, the specific surface area of the metal oxide is 6 m 2 / g~15m 2 / g. In some embodiments, the specific surface area of the metal oxide is 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g or any value in between.
[0030] In some embodiments, the mass ratio of the metal oxide to the silane compound is (3-10):1. In some embodiments, the mass ratio of the metal oxide to the silane compound is 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value therebetween. In some embodiments, the mass ratio of the metal oxide to the silane compound is (6-8):1. If the mass ratio of the metal oxide to the silane compound is too high, the surface modification of the metal oxide will be incomplete, and a large amount of hydrophilic surface will still be exposed; if the mass ratio of the metal oxide to the silane compound is too low, an excess of silane compound will be caused, and the excess silane surface also has hydrophilic groups and is easy to absorb water.
[0031] In some embodiments, based on the total mass of the solid electrolyte layer, the mass percentage of the modified metal oxide is 80% to 97%. In some embodiments, based on the total mass of the solid electrolyte layer, the mass percentage of the modified metal oxide is 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or any value therebetween. In some embodiments, based on the total mass of the solid electrolyte layer, the mass percentage of the modified metal oxide is 83% to 96%.
[0032] In some embodiments, the thickness of the solid electrolyte layer is 1 um to 10 um. In some embodiments, the thickness of the solid electrolyte layer is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value therebetween. In some embodiments, the thickness of the solid electrolyte layer is 1 μm to 5 μm.
[0033] In some embodiments, the solid electrolyte layer further comprises a first binder. The first binder comprises at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylate, polyvinyl alcohol and polyvinylidene fluoride. Based on the total mass of the solid electrolyte layer, the mass percentage of the first binder is 1% to 10%. In some embodiments, based on the total mass of the solid electrolyte layer, the mass percentage of the first binder is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.
[0034] In some embodiments, the solid electrolyte layer also includes: an auxiliary agent, the auxiliary agent including at least one of a dispersant, a wetting agent, a thickener and a defoaming agent; wherein the dispersant includes at least one of polyacrylic acid copolymers, sodium polyacrylate, ammonium polyacrylate, carboxylates and sulfonates; the wetting agent includes at least one of polyether-modified polydimethylsiloxane, sodium perfluoroalkyl sulfonate, polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecyl sulfonate; the thickener includes at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, gelatin, sodium alginate, polyacrylamide and polyvinyl alcohol; the defoaming agent includes polyether-modified polydimethylsilane.
[0035] In some embodiments, based on the total mass of the solid electrolyte layer, the mass percentage of the dispersant is 0.4% to 2%, the mass percentage of the wetting agent is 0.4% to 2%, the mass percentage of the thickener is 0.8% to 5%, and the mass percentage of the defoaming agent is 0.01% to 0.5%. In some embodiments, based on the total mass of the solid electrolyte layer, the mass percentage of the dispersant is 0.4%, 0.5%, 0.7%, 0.9%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2% or any value therebetween, the mass percentage of the wetting agent is 0.4%, 0.5%, 0.7%, 0.9%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2% or any value therebetween The mass percentage of the thickener is 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any value therebetween; the mass percentage of the defoaming agent is 0.01%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or any value therebetween.
[0036] In some embodiments, the diaphragm body includes a base film, and the base film includes at least one of polyethylene (PE), polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), polypropylene (PP), polyimide, aramid and polyethylene terephthalate.
[0037] The thickness of the base film is 5 um to 15 um. In some embodiments, the thickness of the base film is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any value therebetween. In some embodiments, the thickness of the base film is 5 μm to 10 μm.
[0038] In some embodiments, the diaphragm body further includes an inorganic layer, the inorganic layer is disposed between the base membrane and the solid electrolyte layer, and / or the inorganic layer is disposed on the side of the base membrane away from the solid electrolyte layer. That is to say, the diaphragm body may be only a base membrane; or, the diaphragm body may be an inorganic layer disposed on one side of the base membrane, that is, an inorganic layer is disposed on one side; or, the diaphragm body may be an inorganic layer disposed on two opposite surfaces of the base membrane, that is, an inorganic layer is disposed on both sides. When the inorganic layer is disposed on one side, for example, a 2μm inorganic layer is coated on one side, the thickness of the inorganic layer is 2μm; when the inorganic layer is disposed on both sides, for example, an inorganic layer is coated on both sides, and a 2μm inorganic layer is disposed on each side, the total thickness of the inorganic layer is 4μm. Further, when the diaphragm body is only a base membrane, a solid electrolyte layer may be disposed on one side of the base membrane, that is, a solid electrolyte layer is disposed on one side, or a solid electrolyte layer may be disposed on two opposite surfaces of the base membrane, that is, a solid electrolyte layer is disposed on both sides. Specifically, the diaphragm body may be a body that has an inorganic layer disposed on one surface of the base film, and a solid electrolyte layer disposed on the inorganic layer, or a body that has a solid electrolyte layer disposed on the surface of the base film on the side away from the inorganic layer, or a body that has a solid electrolyte layer disposed on both the inorganic layer and the surface of the base film on the side away from the inorganic layer. The diaphragm body may also be a body that has inorganic layers disposed on two opposite surfaces of the base film, a solid electrolyte layer disposed on one inorganic layer, or a body that has solid electrolyte layers disposed on both inorganic layers on both sides.
[0039] In some embodiments, the diaphragm body includes a base membrane and inorganic layers disposed on opposite sides of the base membrane, respectively, and the solid electrolyte layer is disposed on the inorganic layer on one side, and the solid electrolyte layer is disposed toward the negative electrode plate.
[0040] In some embodiments, the inorganic layer includes inorganic particles and a second binder. The inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, boehmite, aluminum hydroxide, garnet, magnesium hydroxide, calcium hydroxide and barium sulfate; the second binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0041] In some embodiments, the thickness of the inorganic layer is 1 um to 5 um. In some embodiments, the thickness of the inorganic layer is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value therebetween.
[0042] 2. Preparation method of diaphragm
[0043] Another aspect of the present application provides a method for preparing a diaphragm, and the diaphragm formed by the preparation method may be the diaphragm described above, and thus may have all the features and advantages of the diaphragm described above, which will not be described in detail here. In some embodiments, the method includes:
[0044] S100: providing a mixed solution containing a silane compound and a first solvent;
[0045] S200: mixing the metal oxide and the mixed solution, and performing a reaction treatment to form a modified metal oxide;
[0046] S300: mixing a second solvent, a modified metal oxide, a first binder and an additive to form a first slurry;
[0047] S400: forming a first slurry on the diaphragm body and forming a diaphragm through a drying process.
[0048] In some embodiments, the first solvent includes at least one of water and ethanol. In some embodiments, the silane compound includes at least one of γ-aminopropyl triethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane, γ-(2,3-epoxypropoxy) propyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane. In some embodiments, the mixed solution also includes at least one of formic acid and acetic acid. Thus, the silane compound can be catalyzed to hydrolyze to form silanol (-Si-OH).
[0049] In some embodiments, the metal oxide includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate, and lithium lanthanum aluminum titanate. Thus, the ionic conductivity of the separator can be improved by using the above metal oxides with high ionic conductivity.
[0050] In some embodiments, the reaction treatment temperature is 20°C to 200°C, and the time is 0.5 hour to 2 hours. In some embodiments, the reaction treatment temperature is 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or any value therebetween, and the time is 0.5 hour, 0.7 hour, 0.9 hour, 1 hour, 1.2 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.8 hours, 2 hours or any value therebetween.
[0051] In some embodiments, the surface of the metal oxide includes hydroxyl groups (-OH), the silane compound contains at least one C1-C6 alkoxy group (-Si-OR, R includes C1-C6 alkyl) connected to the silicon atom, and the silane compound is connected to the surface of the metal oxide by reacting the C1-C6 alkoxy group connected to the silicon atom with the hydroxyl group on the surface of the metal oxide. In some embodiments, the silane compound contains a hydrophobic group, and the hydrophobic group includes at least one of an amine group (-NH2), an alkenyl group (-C=C) and an epoxy group (-C(O)C-). Thus, after the silane compound is connected to the surface of the metal oxide, the hydrophobic group in the silane compound is also synchronously connected to the surface of the metal oxide, and the hydrophobic group can hydrophobically modify the metal oxide, thereby forming a hydrophobic layer on the surface of the metal oxide, reducing the contact and penetration of water with the modified metal oxide powder. It should be noted that the surface of the metal oxide includes hydroxyl groups, which can be introduced when the metal oxide is prepared, that is, a large number of hydroxyl groups will be introduced on the surface when the metal oxide is prepared. The silane compound is a silane coupling agent. When the C1-C6 alkoxy group connected to the silicon atom contained in the silane compound reacts with the hydroxyl group on the surface of the metal oxide, the C1-C6 alkoxy group connected to the silicon atom contained in the silane compound is first hydrolyzed to form a silanol group (-Si-OH). For example, when the silane compound is hydrolyzed in water or ethanol, formic acid or acetic acid can be added to catalyze the hydrolysis. The silanol group formed by the hydrolysis can subsequently react with the hydroxyl group on the surface of the metal oxide, thereby undergoing dehydration condensation. Finally, the silane compound forms a chemical bond through the reaction between the C1-C6 alkoxy group connected to the silicon atom and the hydroxyl group on the surface of the metal oxide, so as to connect the silane compound to the surface of the metal oxide. Therefore, after the metal oxide is surface-modified by a silane compound, the hydrophobic groups in the silane compound are also simultaneously connected to the metal oxide surface to form a hydrophobic layer on the metal oxide surface. When the hydrophobic modified metal oxide is aqueous-coated on the diaphragm body, the contact and penetration of water and the modified metal oxide powder is reduced, and the dispersion properties of the modified metal oxide in oily organic solvents are improved. The resulting diaphragm significantly reduces its moisture value, alleviates the problem of high-temperature gas production in the battery cell caused by high moisture in the diaphragm, and improves the coulombic efficiency and cycle performance of the secondary battery using the diaphragm.
[0052] In some embodiments, after the reaction treatment, the preparation method further comprises filtering and drying in sequence to obtain the modified metal oxide. The filtering and drying processes may be conventional filtering and drying processes in the art, which will not be described in detail herein.
[0053] In some embodiments, the mass ratio of the metal oxide to the silane compound is (3-10): 1. In some embodiments, the mass ratio of the metal oxide to the silane compound is 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1 or any value therebetween. In some embodiments, the mass ratio of the metal oxide to the silane compound is (6-8): 1.
[0054] In some embodiments, based on the total mass of the modified metal oxide, the first binder and the additive, the mass percentage of the modified metal oxide is 80% to 97%. In some embodiments, the mass percentage of the modified metal oxide is 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or any value therebetween.
[0055] In some embodiments, the first binder includes at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylate, polyvinyl alcohol and polyvinylidene fluoride. Based on the total mass of the modified metal oxide, the first binder and the auxiliary agent, the mass percentage of the first binder is 1% to 10%. In some embodiments, the mass percentage of the first binder is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.
[0056] In some embodiments, the auxiliary agent includes at least one of a dispersant, a wetting agent, a thickener and a defoaming agent; wherein the dispersant includes at least one of polyacrylic acid copolymers, sodium polyacrylate, ammonium polyacrylate, carboxylates and sulfonates; the wetting agent includes at least one of polyether-modified polydimethylsiloxane, sodium perfluoroalkyl sulfonate, polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecyl sulfonate; the thickener includes at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, gelatin, sodium alginate, polyacrylamide and polyvinyl alcohol; the defoaming agent includes polyether-modified polydimethylsilane.
[0057] In some embodiments, based on the total mass of the modified metal oxide, the first binder and the auxiliary agent, the mass percentage of the dispersant is 0.4% to 2%, the mass percentage of the wetting agent is 0.4% to 2%, the mass percentage of the thickener is 0.8% to 5%, and the mass percentage of the defoaming agent is 0.01% to 0.5%. In some embodiments, the mass percentage of the dispersant is 0.4%, 0.5%, 0.7%, 0.9%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2% or any value therebetween, the mass percentage of the wetting agent is 0.4%, 0.5%, 0.7%, 0.9%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2% or any value therebetween, the mass percentage of the thickener is 0.8% to 5%, and the mass percentage of the defoaming agent is 0.01% to 0.5%. The mass percentage of is 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any value therebetween, and the mass percentage of the defoaming agent is 0.01%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or any value therebetween.
[0058] In some embodiments, the second solvent includes at least one of water, ethanol, and N-methylpyrrolidone.
[0059] In some embodiments, the drying temperature is 100°C to 300°C, and the time is 1 hour to 24 hours. In some embodiments, the drying temperature is 100°C, 110°C, 120°C, 150°C, 200°C, 220°C, 250°C, 280°C, 300°C, or any value therebetween, and the time is 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 24 hours, or any value therebetween.
[0060] 3. Secondary battery
[0061] Another aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, and the above-described diaphragm or a diaphragm formed by the above-described preparation method; wherein the solid electrolyte layer in the diaphragm is arranged toward the negative electrode sheet. Thus, the secondary battery can have all the features and advantages of the above-described diaphragm or the above-described method, which will not be repeated here.
[0062] In some embodiments, the separator is disposed between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte layer is disposed toward the negative electrode sheet.
[0063] In some embodiments, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a lithium nickel transition metal oxide and a phosphate.
[0064] In some embodiments, the lithium nickel transition metal oxide comprises LiNi x M 1-x At least one of O2, M is selected from at least one of cobalt, manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, yttrium, lanthanum, silver and niobium, 0.1≤x≤1.
[0065] In some embodiments, x is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any value therebetween.
[0066] In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, and Ni95.
[0067] In some embodiments, the phosphate comprises LiMn k B (1-k) PO4, wherein 0≤k≤1, and the B element is selected from at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead. In some embodiments, k is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or any value therebetween. In some embodiments, the phosphate comprises at least one of lithium iron phosphate and lithium iron manganese phosphate. In some embodiments, the phosphate comprises LiMn 0.6 Fe 0.4 PO4 and LiMn 0.8 Fe 0.2 At least one of PO4.
[0068] In some embodiments, the positive electrode active material layer further includes a binder, and optionally a conductive material. The binder improves the bonding of the positive electrode active material particles to each other and also improves the bonding of the positive electrode active material to the current collector.
[0069] In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.
[0070] In some embodiments, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0071] In some embodiments, the positive electrode plate further includes a positive current collector, which may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0072] In some embodiments, the negative electrode plate includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium.
[0073] In some embodiments, the silicon-based material includes at least one of silicon, silicon alloys, silicon oxides, and silicon carbon compounds. In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. In some embodiments, the tin-based material includes at least one of tin, tin oxide, and tin alloys. In some embodiments, the phosphorus-based material includes phosphorus and / or phosphorus compounds.
[0074] In some embodiments, based on the mass of the negative electrode active material, the mass percentage z% of the silicon-based material satisfies: 1≤z≤100. In some embodiments, z is 1, 3, 5, 7, 9, 10, 11, 13, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or any value therebetween.
[0075] In some embodiments, the negative electrode active material layer further includes a binder and a conductive agent. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.
[0076] In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0077] In some embodiments, the negative electrode plate further includes a negative electrode current collector, and the negative electrode current collector includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0078] The secondary battery of the present application also includes an electrolyte. The electrolyte of the present application may be an electrolyte known in the prior art. The electrolyte used in the electrolyte of the present application is not limited, and it may be any electrolyte known in the prior art.
[0079] In some embodiments, the electrolyte includes an organic solvent, a lithium salt, and an optional additive. The organic solvent may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The additive may be any additive known in the prior art that can be used as an electrolyte additive.
[0080] In some embodiments, the organic solvent includes at least one of a linear carbonate, a cyclic carbonate, and a carboxylic acid ester.
[0081] In some embodiments, linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate and fluorinated linear carbonate. In some embodiments, cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate and butylene carbonate. In some embodiments, carboxylate is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, gamma-butyrolactone and fluorinated carboxylate.
[0082] In some embodiments, the mass percentage of the solvent is 40% to 80% based on the mass of the electrolyte. In some embodiments, the mass percentage of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage of the solvent is 50% to 70%.
[0083] In some embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), trifluorosulfonyl lithium (LiTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium bis(fluoromalonate)borate (LiBFMB), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalatophosphate) and lithium 4,5-dicyano-2-(trifluoromethyl)imidazole (LiTDI).
[0084] In some embodiments, the mass percentage of lithium salt is 4% to 25% based on the mass of the electrolyte. In some embodiments, the mass percentage of lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage of lithium salt is 6% to 18%.
[0085] In some embodiments, the additive includes at least one of a cyclic carbonate containing a carbon-carbon double bond, a silyl-containing phosphate, a silyl-containing borate, a nitrile compound, and a propanesulfonic acid pyridinium salt. In some embodiments, the additive is selected from at least one of vinylene carbonate (VC), vinyl ethylene carbonate, tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), succinonitrile, adiponitrile, glutaronitrile, and hexanetrinitrile. In some embodiments, the additive further includes at least one of methylene methyl disulfonate (MMDS), ethylene ethyl disulfonate, 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), diethylene sulfate (DTD), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES).
[0086] In some embodiments, the mass percentage of the additive is 0.05% to 10% based on the mass of the electrolyte. In some embodiments, the mass percentage of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage of the additive is 0.1% to 5%.
[0087] In some embodiments, the preparation method of the secondary battery includes providing an electrode assembly, injecting, packaging and forming. In some embodiments, the temperature of the formation is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C.
[0088] In some embodiments, the formation comprises: charging to 4.25V at 0.05C current and standing for 60 minutes at a temperature of 40°C to 50°C, such as 45°C, and a pressure of 150kgf to 250kgf, such as 210kgf, followed by charging to 4.25V at 0.1C, and then discharging to 3.0V at 0.2C.
[0089] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0090] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0091] In some embodiments, the shape of the secondary battery is not particularly limited, and it may be cylindrical, square, or any other shape.
[0092] In some embodiments, the present application also provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0093] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0094] 4. Device
[0095] Another aspect of the present application provides a device, which includes at least one of the secondary battery, battery module and battery pack described above. Therefore, the device can have all the features and advantages of the secondary battery, battery module or battery pack described above, which will not be repeated here.
[0096] In some embodiments, the device includes, but is not limited to: an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, or a power storage system, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0097] In other embodiments, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0098] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0099] Examples and Comparative Examples
[0100] Example 1
[0101] The preparation steps of the modified metal oxide are as follows: γ-aminopropyltriethoxysilane coupling agent (KH550) and water are mixed, stirred at 50°C for 2 hours to obtain a mixed solution, lithium aluminum titanium phosphate (LATP) and KH550 are added to the mixed solution at a weight ratio of 100:15, reacted at 150°C for 1 hour, then cooled to room temperature, washed, dried, and excess silane coupling agent was removed to obtain hydrophobically modified LATP.
[0102] Diaphragm body: A polyethylene PE base film is used, and a ceramic layer is coated on each of the two opposite surfaces of the PE base film, that is, a double-sided ceramic layer is formed. The ceramic layer is aluminum oxide (Al2O3), the PE base film thickness is 9μm, the ceramic layer thickness is 2μm, and the double-sided thickness is 4μm in total, thus obtaining a ceramic diaphragm body (Al2O3 / PE / Al2O3).
[0103] Preparation steps of the diaphragm: add polyacrylic acid dispersant to water, stir and disperse evenly; then add hydrophobic modified LATP, stir and disperse evenly, grind with a sand mill to obtain a powder dispersion; mix the powder dispersion with sodium carboxymethyl cellulose CMC thickener, polyacrylate PAA binder and silicone wetting agent, stir thoroughly with a stirrer to obtain the final coating slurry; apply the slurry on the diaphragm body through a micro-gravure coating process to form a solid electrolyte layer (1μm thick modified LATP); wherein the mass ratio of each component is hydrophobic modified LATP: binder: dispersant: wetting agent: thickener = 100:4:1:0.5:1.5. The final diaphragm structure is 2μm Al2O3 / 9μm PE base film / 2μm Al2O3 / 1μm modified LATP (Al2O3 / PE / Al2O3 / modified LATP) stacked in sequence.
[0104] The preparation steps of the positive electrode plate are as follows: the positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2, CNT (conductive carbon nanotube) / Super-P (conductive carbon black), binder polyvinylidene fluoride PVDF, by weight ratio LiNi 0.9 Co 0.05 Mn 0.05 O2: CNT / Super-P: PVDF = 95: (2.0 / 1.0): 2 is fully homogenized in N-methylpyrrolidone NMP and coated on a 12 μm thick aluminum current collector, and then dried, rolled, hot pressed and other steps to obtain the positive electrode sheet.
[0105] The preparation steps of the negative electrode sheet are as follows: add the negative electrode active material silicon oxide (SiOx, 0.5≤x≤1.5)-graphite composite (Si / C=14:86), conductive agent acetylene black, binder styrene butadiene rubber SBR, thickener sodium carboxymethyl cellulose CMCNa, and polyacrylate PAA in a weight ratio of 95:2:1.5:1:0.5 to deionized water, and after sufficient homogenization, apply it on a 6μm thick copper current collector, and then obtain the negative electrode sheet through drying, rolling, hot pressing and other steps. Among them, the specific surface area of the negative electrode active material (silicon oxide-graphite composite) is 1.4m 2 / g.
[0106] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), fully dissolve the lithium salt LiPF6 in a mixed solution of EC / DEC / EMC (ethylene carbonate / diethyl carbonate / ethyl methyl carbonate) = 25 / 20 / 55 to prepare a 1 mol / L solution, and stir evenly to obtain the electrolyte.
[0107] Preparation of lithium-ion secondary batteries: The prepared positive electrode sheet, separator (Al2O3 / PE / Al2O3 / modified LATP), and negative electrode sheet are overlapped in sequence, with the separator located between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte layer in the separator is arranged toward the negative electrode sheet (that is, the modified LATP in the separator is arranged toward the negative electrode sheet), and the bare battery cell is wound, and the bare battery cell is placed in a punched aluminum-plastic film soft package shell, and after being fully dried, the prepared electrolyte is injected, and the battery is left at 45°C for 48h, formed in a high-temperature fixture (formation conditions are: temperature 45°C, pressure 210kgf, 0.05C current charged to 4.25V and left to stand for 60min, then 0.1C charged to 4.25V, and then 0.2C discharged to 3.0V, and so on, repeated three times) and secondary sealing, and then conventional capacity division is carried out.
[0108] Examples 2 to 9 and Comparative Examples 1 to 2
[0109] Examples 2 to 9 and Comparative Examples 1 to 2 are achieved by adjusting the type and amount of metal oxide, the type and amount of silane compound, the structure and material of the diaphragm body, etc. on the basis of Example 1. The specific adjustment measures and detailed data are shown in Table 1. Among them, when the diaphragm body is Al2O3 / PE, the solid electrolyte layer is arranged on the surface of the PE side away from Al2O3.
[0110] Test Method
[0111] 1. Contact angle test
[0112] A 5 μL droplet was used to titrate on the solid electrolyte layer whose contact angle was to be measured. After the titration was completed, the contact angle after standing for 10 seconds was measured using a contact angle tester. The titrated droplet was an electrolyte, the solvent of the electrolyte was EC:EMC:DMC=1:1:1, and the lithium salt was 1 mol / L LiPF6.
[0113] 2. Moisture test
[0114] The test was conducted using a Karl Fischer moisture tester at a temperature of 150°C for 10 minutes.
[0115] 3. Cycle performance test
[0116] At 25°C, the prepared lithium-ion secondary battery was charged to 4.2V at a constant current rate of 1C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 1C, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 300 times by the above method, and the discharge capacity was recorded each time. The capacity retention rate of the lithium-ion secondary battery after 300 cycles at 25°C = the discharge capacity of the 300th time / initial discharge capacity × 100%.
[0117] 4. Ionic conductivity test
[0118] Assemble the buckle: stainless steel sheet / diaphragm / stainless steel sheet; use EIS (electrochemical impedance spectroscopy) to test the ionic conductivity, the test conditions are: 5mV, 1MHz~0.01Hz.
[0119] Test Results
[0120] Table 1
[0121]
[0122] It can be seen from Examples 1 to 9 and Comparative Examples 1 to 2 that after the metal oxide is surface-modified with a silane compound, a hydrophobic layer is formed on the surface of the metal oxide, and the contact angle of the solid electrolyte layer is significantly improved, and the hydrophobic effect is good. When the hydrophobic modified metal oxide is coated on the diaphragm body, the contact and penetration of water and the modified metal oxide powder are reduced, and the resulting diaphragm significantly reduces its moisture value; and the cycle performance of the secondary battery using the diaphragm is improved. In addition, the solid electrolyte layer in the diaphragm can reduce the migration of transition metal ions (such as manganese elements) dissolved from the positive electrode plate side to the surface of the negative electrode plate, improve the stability of the SEI film on the surface of the negative electrode plate, reduce side reactions, and thus improve the safety performance and cycle performance of the battery.
[0123] Comparison with Example 1 shows that although a solid electrolyte layer containing metal oxide is provided in the diaphragm, the metal oxide is not modified, and the surface is not connected to a silane compound, so the contact angle of the surface of the solid electrolyte layer is small, the hydrophobicity is poor, the moisture content of the diaphragm is high, and the cycle performance of the secondary battery using the diaphragm is general. Comparison with Example 2 shows that no solid electrolyte layer containing metal oxide is provided in the diaphragm, and only a conventional alumina ceramic diaphragm is used. Although the moisture content of the diaphragm is low (although the ceramic diaphragm is hydrophilic, it is easier to remove after drying), however, the ionic conductivity of the diaphragm is low, which will lead to an increase in the internal resistance of the secondary battery using the diaphragm, and since no solid electrolyte layer containing metal oxide is provided in Comparative Example 2, it is impossible to achieve the reduction of the transition metal ions (such as manganese elements) dissolved from the positive electrode plate side to migrate to the surface of the negative electrode plate in the present application, thereby affecting the cycle performance of the secondary battery.
[0124] Figure 1 Schematic diagram of contact angle test of the diaphragm of comparative example 1. Figure 2 Schematic diagram of the contact angle test of the diaphragm of Example 1. Figures 1-2It can be seen that compared with the diaphragm formed by the unmodified metal oxide in Comparative Example 1, the contact angle of the diaphragm in the present application is significantly larger than the contact angle tested in Comparative Example 1, indicating that after the modification, the hydrophobicity of the solid electrolyte layer is significantly enhanced, the moisture value in the diaphragm is significantly reduced, the high-temperature gas production problem of the battery cell caused by high moisture in the diaphragm is alleviated, and the coulombic efficiency and cycle performance of the secondary battery using the diaphragm are improved.
[0125] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A diaphragm, characterized in that: include: diaphragm body; A solid electrolyte layer, wherein the solid electrolyte layer is arranged on the diaphragm body, the solid electrolyte layer includes a modified metal oxide, and the modified metal oxide includes a metal oxide and a silane compound connected to the surface of the metal oxide, wherein the metal oxide includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium lanthanum aluminum titanate.
2. The diaphragm according to claim 1, characterized in that The surface of the metal oxide includes hydroxyl groups, the silane compound contains at least one C1-C6 alkoxy group connected to a silicon atom, and the silane compound is connected to the surface of the metal oxide through a reaction between the C1-C6 alkoxy group connected to the silicon atom and the hydroxyl group on the surface of the metal oxide; and / or The silane compound contains a hydrophobic group, wherein the hydrophobic group includes at least one of an amine group, an alkenyl group and an epoxy group; and / or The contact angle of the modified metal oxide is 80° to 120°; and / or The ion conductivity of the separator is 0.5 ms / cm to 0.9 ms / cm.
3. The diaphragm according to claim 1 or 2, characterized in that: The silane compound includes at least one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
4. The diaphragm according to claim 1 or 2, characterized in that: The contact angle of the modified metal oxide is 100° to 120°; and / or The average particle size of the metal oxide is 0.3 μm to 3 μm; and / or The specific surface area of the metal oxide is 6 m 2 / g~15m 2 / g; and / or The mass ratio of the metal oxide to the silane compound is (3-10):1; and / or Based on the total mass of the solid electrolyte layer, the mass percentage of the modified metal oxide is 80% to 97%; and / or The thickness of the solid electrolyte layer is 1 um to 10 um.
5. The diaphragm according to claim 1, characterized in that The solid electrolyte layer further comprises: a first binder, wherein the first binder comprises at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylate, polyvinyl alcohol and polyvinylidene fluoride; based on the total mass of the solid electrolyte layer, the mass percentage of the first binder is 1% to 10%; and / or The auxiliary agent comprises at least one of a dispersant, a wetting agent, a thickener and a defoamer; wherein the dispersant comprises at least one of a polyacrylic acid copolymer, sodium polyacrylate, ammonium polyacrylate, a carboxylate and a sulfonate; the wetting agent comprises at least one of polyether-modified polydimethylsiloxane, sodium perfluoroalkyl sulfonate, polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecyl sulfonate; the thickener comprises at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, gelatin, sodium alginate, polyacrylamide and polyvinyl alcohol; the defoamer comprises polyether-modified polydimethylsilane; wherein, based on the total mass of the solid electrolyte layer, the mass percentage of the dispersant is 0.4% to 2%, the mass percentage of the wetting agent is 0.4% to 2%, the mass percentage of the thickener is 0.8% to 5%, and the mass percentage of the defoamer is 0.01% to 0.5%.
6. The diaphragm according to claim 1, characterized in that The diaphragm body comprises a base film, and the base film comprises at least one of polyethylene, a polypropylene / polyethylene / polypropylene three-layer composite film, polypropylene, polyimide, aramid and polyethylene terephthalate; The thickness of the base film is 5um to 15um.
7. The diaphragm according to claim 6, characterized in that The diaphragm body further comprises an inorganic layer, wherein the inorganic layer is disposed between the base film and the solid electrolyte layer, and / or the inorganic layer is disposed on a side of the base film away from the solid electrolyte layer; Wherein, the inorganic layer includes inorganic particles and a second binder; the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, boehmite, aluminum hydroxide, garnet, magnesium hydroxide, calcium hydroxide and barium sulfate; the second binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene; The thickness of the inorganic layer is 1 um to 5 um.
8. A method for preparing a diaphragm, characterized in that: include: providing a mixed solution containing a silane compound and a first solvent; Mixing a metal oxide with the mixed solution and treating by reaction to form a modified metal oxide; wherein the metal oxide comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium aluminum lanthanum titanate; Mixing a second solvent, the modified metal oxide, a first binder and an auxiliary agent to form a first slurry; The first slurry is formed on a diaphragm body and dried to form the diaphragm.
9. The preparation method according to claim 8, characterized in that: The first solvent comprises at least one of water and ethanol; and / or The mixed solution further comprises at least one of formic acid and acetic acid; and / or The second solvent comprises at least one of water, ethanol and N-methylpyrrolidone; and / or The reaction treatment temperature is 20°C to 200°C, and the reaction time is 0.5 hours to 10 hours; and / or After the reaction treatment, the preparation method further comprises sequentially performing a filtration treatment and a drying treatment to obtain the modified metal oxide; and / or The drying process is performed at a temperature of 100° C. to 300° C. and for a time of 1 hour to 24 hours.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator according to any one of claims 1 to 7 or a separator formed by the preparation method according to any one of claims 8 to 9; Wherein, the solid electrolyte layer in the diaphragm is arranged toward the negative electrode plate.
Citation Information
Cited By
Solid-state battery and preparation method thereof, battery device, power utilization device and energy storage device
CN120999135A